2023
DOI: 10.3390/ma16062422
|View full text |Cite
|
Sign up to set email alerts
|

Review of Play and Preisach Models for Hysteresis in Magnetic Materials

Abstract: This paper studies the properties of the Preisach model and the play model, and compare their similarities. Both are history-dependent hysteresis models that are used to model magnetic hysteresis. They are described as discrete sums of simple hysteresis operators but can easily be reformulated as integral equations of continuous distribution functions using either a Preisach weight distribution function or a play distribution function. The models are mostly seen as phenomenological or mathematical tools but ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 257 publications
0
20
0
Order By: Relevance
“…In our experiment, ΔT ≈ 17 K and ΔT u ≈ 30 K, thus we obtain the evaluated parameters g c0 = 1400 J/kg, σ c = 300 J/kg, and σ u = 850 J/kg. Next, we use the Preisach model 51,52 to analyze the SAWinduced FeRh MPT. Preisach model is a famous historydependent hysteresis model developed in 1935 by Preisach.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, ΔT ≈ 17 K and ΔT u ≈ 30 K, thus we obtain the evaluated parameters g c0 = 1400 J/kg, σ c = 300 J/kg, and σ u = 850 J/kg. Next, we use the Preisach model 51,52 to analyze the SAWinduced FeRh MPT. Preisach model is a famous historydependent hysteresis model developed in 1935 by Preisach.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the inverse model, B(t) is the input and H(t) is the output. There are mainly three physical processes that cause the hysteresis effect in magnetic materials [151]: domain wall motions [151][152][153][154] and the nucleation of domain walls [151]. Many different models have been proposed to explain the hysteresis behaviour in materials with small and large grain sizes.…”
Section: Advanced Mathematical Models For the Hysteresismentioning
confidence: 99%
“…These methodologies can be categorised in many ways. Mörée showed that most of them can be mathematically described as Play-and Preisach-type models [151]. The most-general model is the Preisach model because it allows the inclusion of saturation and variations of the hysteresis [151].…”
Section: Advanced Mathematical Models For the Hysteresismentioning
confidence: 99%
“…The concept of the Preisach hysteresis model was proposed by the German physicist F. Preisach in 1935. After improved by several researchers, the classical Preisach model with mathematical expressions was later widely used [ 1 , 2 , 3 ]. The Preisach model can be classified into continuous models and discrete models.…”
Section: Introductionmentioning
confidence: 99%